2001
DOI: 10.1097/00005768-200112000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant production and immune response after stretch injury in skeletal muscle

Abstract: We conclude that acute muscle stretch injury and the required surgeries to generate the injury result in a biphasic increase in oxidant production in both injured and control limbs, suggesting a systemic immune response. The increase in oxidant production at 4 h may be caused by an increase in activated neutrophils, whereas XO activity may contribute to oxidant generation at 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 27 publications
1
46
0
2
Order By: Relevance
“…One possibility is that the enhanced expression of iNOS was caused by the infiltration and activation of neutrophils, which are known to release inflammatory cytokines [26]. Consistent with this hypothesis, our previous study showed an increase in myeloperoxidase activity, a biochemical marker for neutrophil presence, in injured muscles at 4 h and 48 h following injury [27]. Neutrophils undergo the respiratory burst to generate reactive oxygen species as signaling molecules to activate the nuclear factor (NFκB) and, in turn, iNOS activation [28].…”
Section: Macrophage Lysate Was Used As a Positive Control (Pc) (B)supporting
confidence: 54%
See 1 more Smart Citation
“…One possibility is that the enhanced expression of iNOS was caused by the infiltration and activation of neutrophils, which are known to release inflammatory cytokines [26]. Consistent with this hypothesis, our previous study showed an increase in myeloperoxidase activity, a biochemical marker for neutrophil presence, in injured muscles at 4 h and 48 h following injury [27]. Neutrophils undergo the respiratory burst to generate reactive oxygen species as signaling molecules to activate the nuclear factor (NFκB) and, in turn, iNOS activation [28].…”
Section: Macrophage Lysate Was Used As a Positive Control (Pc) (B)supporting
confidence: 54%
“…Using a similar injury protocol, we previously reported an increase in the rate of oxidant production at 24 h after operation and injury in the sham-operated and stretch-injured muscles [27]. This increase paralleled an increase in xanthine oxidase activity, suggesting that O 2…”
Section: Macrophage Lysate Was Used As a Positive Control (Pc) (B)mentioning
confidence: 69%
“…The mean value was significantly different from that of the control trial: * P < 0·05, ** P < 0·01. phagocytes progressively accumulate in the muscle and initiate inflammatory events that precede tissue repair, including releasing reactive species that can help degrade cellular debris (2,(33)(34)(35)(36) . It has been assumed that reactive species released by phagocytes could occasionally act on intact structures, leading to additional damage and delayed recovery of muscle strength (3,(5)(6)(7)(8)33) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been assumed that reactive species released by phagocytes could occasionally act on intact structures, leading to additional damage and delayed recovery of muscle strength (3,(5)(6)(7)(8)33) . Neutrophils are the first phagocytes to invade the muscle, typically peaking in concentration between 6 and 24 h after damage and then quickly decreasing in numbers (8,(34)(35)(36) . Phagocytic macrophage concentrations are elevated at 24 h and peak about 48 h after injury (6,35,36) .…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the muscle fiber increases the release of calcium (Ca 2 +), leading to the synthesis of pro-inflammatory cytokines, including tumor necrosis factor alpha (TNF-α) and IL-1β, which regulate the expression of selections by the endothelial cells that attract circulating neutrophils to the region. IL-6 and IL-8 cytokines, which are secreted after tissue damage, stimulate the signaling pathway that activates NADPH-oxidase causing the release of reactive oxygen species 40 . Wolach et al 41 examined the effect of anaerobic exercise (Wingate test) and aerobic exercise (performed at 70-80% of HRmax) on the function of neutrophil in female judo athletes compared to sedentary women.…”
Section: Physical Exercise Effect On Cells Of the Immune System Neutrmentioning
confidence: 99%